Extending Shelf Life of Indonesian Soft Milk Cheese (Dangke) by Lactoperoxidase System and Lysozyme - Ahmad Ni’matullah Al-Baarri; Anang Mohamad Legowo; Septinika Kurnia Arum; Shigeru Hayakawa (International Journal of Food Science)
Dangke, a type of fresh soft cheese made of bovine and buffalo milk, is a traditional dairy product used in South Sulawesi, Indonesia. It is prepared from fresh milk using the conventional method, which easily destroys the quality. This study was conducted to assess whether using lactoperoxidase system and lysozyme as preservative agents could suppress the growth of bacteria in dangke. The pH value, total microbial count, and hardness of dangke were determined to measure the quality. Lactoperoxidase and lysozyme were purified from fresh bovine milk, and their purity was confirmed using SDS-PAGE. The combination of lactoperoxidase system and lysozyme was able to remarkably suppress the total microbial count in dangke from 7.78±0.67 to 5.30±0.42 log CFU/ml during 8 h of storage at room temperature. Preserving dangke in this enzyme combination affected its hardness, but there was no remarkable change in the pH value. Results of this study may provide knowledge to utilize a new method to preserve the quality of dangke.